Konsep Bimbingan Perkawinan Pra Nikah Untuk Mengurangi Tingginya Perceraian Karena Reuni Di Sumatera Barat - Andalusia, Andalusia; Yasniwati, Yasniwati (Nagari Law Review, 2024)
The incidence of divorce in Indonesia has once again surged. According to the Indonesian Statistics report, the total number of divorce cases in the nation reached 447,743 in 2021, marking a 53.50% increase from 2020's 291,677 cases. This report reveals that a larger proportion of wives initiate divorce proceedings compared to husbands. Specifically, 337,343 cases, or 75.34% of divorces, were a result of contested divorce, where the wife filed a lawsuit that was adjudicated by the Court. On the other hand, 110,440 cases, or 24.66% of divorces, stemmed from uncontested divorce, where the husband filed a petition that was decided by the Court. Geographically, West Java recorded the highest number of divorce cases in 2021 at 98,088, followed by East Java and Central Java with 88,235 and 75,509 cases respectively. The primary catalyst for divorce in 2021 was persistent conflicts and arguments, accounting for 279,205 cases. Additionally, economic factors, abandonment, domestic violence, and even polygamy were cited as reasons for divorce. Over the past five years, divorce trends in Indonesia have exhibited fluctuations, with the highest number of cases recorded in 2021, and the lowest in 2020. Notably, divorce rates experienced a significant spike from 2017 to 2019. West Sumatra ranks as the 10th province with the highest number of divorces in Indonesia, totaling 9,371 cases, comprising 2,372 divorces and 6,999 lawsuit divorces. This data raises concerns about the state of our community's households.